How staying in a single room affects the experiences of haematology inpatients in an Australian cancer hospital. (10th March 2022) - Bishop, Emma; Miller, Charne; Miller, Sam; McKellar, Catherine
Abstract : Background: It has been suggested that single rooms for patients improve patient dignity and privacy and reduce infection transmission, but they can be socially isolating. It is not well understood how single rooms affect long-stay patients. Aims: To understand the experience of being an inpatient in a ward with single-room design. Methods: A qualitative, phenomenological study was conducted using semi-structured interviews with patients ( n =10) in a newly built cancer hospital with a 100% single-room haematology ward. Interviews were analysed using Colaizzi's (1978) seven-step analysis. Findings: Patients described their experiences of their acute stay using the concepts of privacy, isolation and independence, as well as enabling sleep. Privacy enabled patients to have their own toilet, was perceived to aid infection control and provided silence. Privacy came at a cost of isolation, but patients re-framed this as expected and necessary for self-preservation. Furthermore, they were unsure as to whether other patients would reciprocate social contact and instead relied on the healthcare team. Patients sought independence during their acute stay as it enabled them to control the environment and create a space for healing. The ability to sleep and be rested was also a critical feature of patients' stay. Conclusion: The research highlighted that haematology patients prefer single rooms. However, because they experienced isolation, it also highlighted the importance of facilitating and enabling peer support within the haematology setting.